2017
DOI: 10.4012/dmj.2016-083
|View full text |Cite|
|
Sign up to set email alerts
|

Influences of filler content and size on the color adjustment potential of nonlayered resin composites

Abstract: The blending effect (BE) plays an important role in esthetics of the composite resin. The objective of this study was to determine the extents to which filler size and content affect the BE. Three types of fillers (0.7, 1.0, and 1.5 µm) were mixed at weight contents of 60, 70, 75, and 80%. This study simulated clinical class 3 or 4 cavities and quantitatively measured the color diffusion of the objects next to the cavities based on the CIELab color space. For each filler size, there was a trend of increasing B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 7 publications
0
54
0
2
Order By: Relevance
“…26 The results from the present study showed 28 Furthermore, the optical behavior of a restoration in the anterior or posterior segment of the dental arcade is different, once the improper level of translucency in anterior restorations can be more affected by the dark background of the oral cavity, resulting in grayish restorations. 17,29 Another parameter that was previously demonstrated to be efficient for color evaluation in a more practical way is the visual scoring. 11,12 The scores found for the composites tested in the present study are positively correlated to the photographic evaluation, once the highest scores demonstrated were also for OC (from 2.73 to 2.87, it means, obvious mismatch) while all the other groups presented lower scores (from 1.13 to 1.83, meaning very good match and not so good match, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 The results from the present study showed 28 Furthermore, the optical behavior of a restoration in the anterior or posterior segment of the dental arcade is different, once the improper level of translucency in anterior restorations can be more affected by the dark background of the oral cavity, resulting in grayish restorations. 17,29 Another parameter that was previously demonstrated to be efficient for color evaluation in a more practical way is the visual scoring. 11,12 The scores found for the composites tested in the present study are positively correlated to the photographic evaluation, once the highest scores demonstrated were also for OC (from 2.73 to 2.87, it means, obvious mismatch) while all the other groups presented lower scores (from 1.13 to 1.83, meaning very good match and not so good match, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…12 These materials have a universal opacity and few Vita shades available, being recommended by developers to be used in a single shade increment that could possibly match different teeth colors. 17 Recently, a single shade universal composite, that could supposedly match all Vita Classical shades, from A1 to D4, was developed. 11,18 A previous study evaluated the CAP of some of these composites in molar class I restorations 11 ; however, the capacity of color matching of this material was not yet investigated in anterior restorations.…”
Section: Introductionmentioning
confidence: 99%
“…Universal composite resins carry fewer shades, (either single‐ or group‐shaded materials) than previous composite resins due to improved “blending in” effect with the tooth structure 153,154 also known as color adjustment potential (CAP) 155 . Composite resins with pronounced color adjustment are able to interact with surrounding enamel and dentin, resulting in reduced color differences.…”
Section: Universal Composite Resinsmentioning
confidence: 99%
“…Previous research has shown that the filler content, shape, and size have an effect on the color of the composite. 23,24,26 This occurs as some of the light is absorbed by the material while a part of it is reflected, which contributes to the color of the material. OM has been developed with a smart chromatic technology which, rather than relying on red and yellow pigments that are added to impart color, it uses the concept of structural color where the material itself weakens or amplifies specific wavelengths of light to blend in.…”
Section: F I G U R Ementioning
confidence: 99%